Compaction of North-Sea Chalk by Pore-Failure and Pressure Solution in a Producing Reservoir - Keszthelyi, Daniel; Dysthe, Dag K.; Jamtveit, Bjørn (Frontiers in Physics, 2016)
The Ekofisk field, Norwegian North sea,is an example of compacting chalk reservoir with considerable subsequent seafloor subsidence due to petroleum production. Previously, a number of models were created to predict the compaction using different phenomenological approaches. Here we present a different approach, we use a new creep model based on microscopic mechanisms with no fitting parameters to predict strain rate at core scale and at reservoir scale. The model is able to reproduce creep experiments and the magnitude of the observed subsidence making it the first microstructural model which can explain the Ekofisk compaction.